MOTIVASI BELAJAR MAHASISWA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNRI DALAM MENGIKUTI PERKULIAHAN ONLINE MBKM KEWIRAUSAHAAN - Rejeki, Yunita Sri; Juita, Ardiah; Aspa, Agus Prima (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2025)
Abstract: The purpose of this study was to determine the learning motivation of students of the Faculty of Teacher Training and Education, UNRI in Following Online Lectures of MBKM Entrepreneurship (Merdeka Belajar-Kampus Merdeka). This study uses a quantitative approach that is descriptive in nature. The place of this research was conducted at the FKIP Campus, Universitas Riau, Jl. Binawidya District. Tampan, Pekanbaru, Riau. It was carried out on July 27, 2024 to September 29, 2024 starting from the questionnaire trial to the research. The research instrument used in this study was in the form of a questionnaire, the researcher conducted a statistical analysis technique calculating the percentage. Based on the results of the study, the conclusions obtained in this study are: The Learning Motivation of Students of the Faculty of Teacher Training and Education, Unri in Following Online Lectures of MBKM Entrepreneurship is included in the range of 50.01 - 75% or in the Good category with a percentage of 72.27%. Keywords: Learning Motivation, Online Lectures